2013
DOI: 10.1007/s11665-013-0806-6
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of Sputtered Nickel Films on Polycarbonate Substrates

Abstract: Nickel films were deposited by radio frequency magnetron sputtering on top of polycarbonate substrates. Surface energy of the substrate was measured by means of the contact angle technique. Effects of sputtering parameters on the critical load between the film and the substrate were determined by the universal mechanical testing system. Optimized fabrication parameters and their influence on the critical load between sputtered nickel films and polymer substrate were studied by means of the orthogonal experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…These cracks have a geometry that accompanies the accumulation of material in front of the indenter, not putting the adhesion of the coating at risk. These results are in line with conclusions obtained by other authors who have studied adhesion to polymers substrates [32,62].…”
Section: Adhesion Evaluationsupporting
confidence: 93%
See 1 more Smart Citation
“…These cracks have a geometry that accompanies the accumulation of material in front of the indenter, not putting the adhesion of the coating at risk. These results are in line with conclusions obtained by other authors who have studied adhesion to polymers substrates [32,62].…”
Section: Adhesion Evaluationsupporting
confidence: 93%
“…However, several studies have been carried out in the application of PVD coatings in polymers, and even in the evaluation of the adhesion and wear resistance of these coatings. Based on ABS (Acrylonitrile Butadiene Styrene) substrates, Qian et al [32] investigated the adhesion of thin Ni coatings carried out by PVD sputtering, considering the parameters used in the deposition. By conducting tests on micro-scratch equipment, it was possible to find that the greater the ionization energy used in the process, the later the critical failure in the coating occurs.…”
Section: Introductionmentioning
confidence: 99%
“…If the substrate is hard and brittle, the substrate may break before the film not measuring the interfacial toughness of the thin film as was seen in publication III. (Sang-Hyuk, 2001;Qian, 2014 1. De-cohesion (through-thickness fracture): The film can undergo Hertzian cracking or crack under tensile stress behind the indenter.…”
Section: Loading To the Top Of The Film-substrate Interfacementioning
confidence: 99%
“…The authors studied the HiPIMS method to coat the ABS surface and in a comparative study, they concluded that the CrN coating deposited by HiPIMS had a higher corrosion and mechanical resistance than that applied by DCMS, making clear the possibility of this method to replace Cr electroplating in polymers. Qian et al [21] deposited Ni thin films by sputtering in PC substrates to study the adhesion of the film as a function of the process parameters. Through micro-scratch equipment, the authors were able to state that the greater the ionization energy, the later the critical failure in the coating occurs, but in a larger study, the authors also performed plasma steps to increase the surface energy of the substrate and were able to conclude that this stage was the most important regarding the influence of the critical load that the coating is able to support, thus improving the adhesion between Ni and PC.…”
Section: Introductionmentioning
confidence: 99%